THE INFLUENCE OF FINANCIAL LITERACY, HEDONISME LIFESTYLE, AND FINANCIAL SELF EFFICACY ON FINANCIAL BEHAVIOR - Suryanti; Fityan Izza Noor Abidin (International Journal of Business, Law and Political Science, 2025)
Objective: This research was carried out with the aim of finding out the influence of financial literacy on financial behavior, to find out the influence of a hedonistic lifestyle on financial behavior, and to find out the influence of financial self-efficacy on financial behavior. Method: This research method uses quantitative, data collection is carried out by distributing questionnaires via Google Form, and the sampling technique used is purposive sampling. Result: The results of this research show that there is a significant influence between Financial Literacy and Financial Behavior, there is a significant influence between the Hedonistic Lifestyle and Financial Behavior, and there is a significant influence between Financial Self-Efficacy and Financial Behavior. Novelty: This study highlights the combined impact of financial literacy, hedonistic lifestyle, and financial self-efficacy on financial behavior.